Synergies between the Food System Resilience Program (FSRP) and the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) in West Africa: implementation domains for cross-fertilization - Zougmoré, Robert B.; Ali, Abdou; Lamien, Niéyidouba; Segnon, Alcade C; Freeman, Katie Kennedy (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Through action research across six anchored countries in Africa, AICCRA aims at scaling access and use of enhanced climate information services (CIS) and evidence-based climate-smart agriculture (CSA) technologies and innovations for effective climate risk management and sustainable productivity improvement in various agricultural value chains and sub-sectors. FSRP is a major climate-resilient development program that makes effective use of this new generation of climate information services to improve climatic and disaster risk management, and the application of climate-smart agriculture innovations to improve the agricultural productive base in West African food systems. Fostering synergy between FSRP and AICCRA offers a great spillover opportunity to scale up climate services and climate-smart agriculture to benefit all CILSS-ECOWAS member countries and beyond. As two World Bank-funded projects within the same region and built under a long-term programmatic approach, FSRP and AICCRA are two unique programs to strengthen the institutional capacities and make economy of scale while fostering cross-fertilization among IDA funded-projects in West Africa. From an operational point of view, the active participations, and interactions of both projects’ stakeholders to their respective activities, events and statutory meetings bolster effectiveness of these synergies. The synergies between these two sister projects pave the way for fostering not only the uptake but more importantly the effective use of science-evidenced CSA innovations and CIS across West Africa and the Sahel